AcadEvent: Recommender system for academic events - Othman, W.S.N.A.W.; Mohd Shuib, N.L.; Normadhi, N.B.A. (2017)
Academic events are events that are commonly organized in an educational environment such as workshops, seminars or conferences. Finding suitable academic events for researchers, especially novice researchers, is a crucial task. However, the dissemination of information on academic events is still limited. Existing tools are inadequate to provide recommendations based on user needs as these tools have limited functions. Hence, there is a need to develop a recommender system that recommends suitable, relevant and reliable academic events to the researcher. The aim of this paper was to propose a hybrid recommender technique to assist novice researchers in finding suitable, relevant and reliable academic events. This paper presents the architecture for AcadEvent, a recommender system for academic events using a hybrid technique consisting of a search based on Tags and a User Rating. The research methodology was comprised of four stages, namely information requirements, technique development, prototype development, and evaluation. The evaluation results showed that the proposed technique offers a better performance in terms of assisting the researcher in finding suitable and relevant academic events.